(3GdJMhGdJ GdadSajI ai GdCNdGbjGJ GdHjhWHjI (B= s Philosophical shifts in biomedical ethics - (3TjeGA YWjI EeGe s; (3CMeO YHOGdMdje YWjI (B: s; (3YeQ CMeO GdcGTa (B: s ((3GdbGgQI (B: s (3TjeGA YWjI EeGe (B: s, 2016)
(3eY bUhQ dZI GdeHGOF Yf GdJYGed eY GdJfhY hGdKQGA GdKbGai GdehLhO Hjf GdLeGYGJ hGdeLJeYGJ GdeNJdaI JYQVJ GdGNdGbjGJ GdHjhWHjI dfbO ef bHd eacQi hadGSaI eG HYO GdMOGKI HSHH JMjRgG OGNd GdKbGaI GdGfLdh (B- (3GeQjcjI hJLGgdgG dOhQ Gdbje GdKbGajI hGdeYJbOGJ GdOjfjI GdeNJdaI ai JTcjd GdacQ GdHjhGNdGbi Gf GdJZPjI dG eQcRjI GdKbGaI jLH Gf Jchf gi GdQcjRI GdGSGSjI ai GdJYGed eY GdGTcGdjGJ GdSjGSjI hGdGLJeGYjI hGdGNdGbjI GdfGJLI Yf GSJNOGe JbfjGJ GdHjhdhLjG hGdgfOSI GdhQGKjI ai eLGd GdQYGjI GdUMjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdadSaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCNdGbjGJ GdHjhWHjI s; (3GdGfKQHhdhLjG GdKbGajIs; (3GdJZPjI GdKbGajI s